Thromboelastography in Patients with Inflammatory Bowel Disease. (20th May 2020) - Shen, Yonghua; Shi, Liangliang; Zhang, Juanjuan; Zhu, Hao; Yao, Yuling; Liu, Zhenqing; Zou, Xiaoping; Zhang, Xiaoqi
Abstract : Purpose . Patients with inflammatory bowel disease (IBD) frequently suffer from venous thromboembolic events, and the risk of thromboembolism increases along with disease activity. This study was conducted to discover novel thrombophilic markers using thromboelastography (TEG) and to evaluate the relation between the predisposing factors and the activity of disease in Chinese patients with Crohn's disease (CD) and ulcerative colitis (UC). Methods . Thirty-four patients with CD, 29 patients with UC, and 53 healthy volunteers were enrolled into this study. Blood levels of R, K, α Angle, G, maximal amplitude (MA), and LY30 with TEG were determined. Results . Mean values of R, K, α Angle, G, and MA were significantly different in patients with CD and UC compared with the healthy individuals. Patients with active CD had different K, α Angle, G, and MA levels compared with patients in remission (P < 0.05, P < 0.001, P < 0.001, and P < 0.001 ). Levels of R, α Angle, G, and MA were also significantly different in active UC patients compared with those in remission (P < 0.01, P < 0.001, P < 0.001, and P < 0.001 ). Except for the G level in the CD group, differences in all TEG levels between healthy individuals and IBD patients in remission were not statistically significant. No statistical differences were observed in LY30 among patients with active phase, patients in remission, and the healthy individuals. Conclusion . Thrombophilic defects are common in Chinese patients with IBD, and TEG can be considered a new direction to anticoagulant thromboprophylaxis in IBD.